2009
DOI: 10.1007/s00228-009-0730-8
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of intravenous ondansetron in oncology and surgical patients aged 1−48 months

Abstract: The population pharmacokinetic analysis of ondansetron allows for characterization of individual patients based on body weight and age. It is recommended that patients younger than 4 months receiving ondansetron be closely monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Our findings are consistent with the pharmacokinetic properties of ondansetron that were measured in other nonpregnant adult populations. Our finding that ondansetron kinetics follow a biexponential disposition, and the measured clearance parameters ( Table ), are in good agreement with previously reported results . Because 95% of ondansetron's clearance is mediated by hepatic oxidation, the dose‐dependent clearance is probably due to saturation of hepatic metabolic enzymes, as previously reported .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings are consistent with the pharmacokinetic properties of ondansetron that were measured in other nonpregnant adult populations. Our finding that ondansetron kinetics follow a biexponential disposition, and the measured clearance parameters ( Table ), are in good agreement with previously reported results . Because 95% of ondansetron's clearance is mediated by hepatic oxidation, the dose‐dependent clearance is probably due to saturation of hepatic metabolic enzymes, as previously reported .…”
Section: Discussionsupporting
confidence: 92%
“…Because an external ondansetron dose was not administered to neonates, it was not possible to uniquely identify clearance or volume of distribution. However, the assumption of equal distribution volumes in neonates and 1–48‐month‐old infants is valid, since the birthweight of our neonates is in range of the weights studied by Mondick et al …”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…[22][23][24][25][26][27][28][29] Other studies reported efficacy of the drug in pediatric surgical or oncology patients. [30][31][32][33][34][35][36][37][38][39] One of those studies reported mild, asymptomatic QT prolongations that remained within normal limits. 31 A literature search was performed for reports of ventricular arrhythmias, fatalities, or any type of toxicity thought to be related to ondansetron in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%